Stop teaching : principles and practices for responsible management education - Rimanoczy, Isabel, 1956- (Principles for responsible management education collection., 2016)
What do we need to change in order to develop a new generation of business leaders who connect profits with purpose, who see in social entrepreneurship and innovation the key opportunity for addressing our planetary challenges? The answer lays in the contents we select to teach, in the values we invite to explore and develop, and in the methods we use. In the era of 24/7 global access to information from our mobile gadgets, many institutions of higher education are still sitting students in rows or amphitheaters, measuring success via tests and evaluations, with instructors lecturing what students should learn. And instructors feel the challenge of competing with sleepy audiences that divide their attention between their cell phones and the speaker. Stop teaching, the author says, inviting instructors in management schools and higher education to adopt some proven learning principles that can reengage students, unleash their potentials, and foster them to shape the world they want to live in. And have fun doing it. Through adult learning research, guides, activities, and stories from pioneering learning facilitators in education and corporate training, Rimanoczy brings a long-needed revamp to educational institutions that want to be part of responsible management education.